The Influence of Broken Families on Student Deviant Behavior in State Junior High School 2 Plered - mulidah, nyai; Saleh, Abdurrahman (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2022)
In the world of education, schools are not fully a determinant of the success of students, but the participation and encouragement of parents is a factor in achieving educational goals. The existence of the family is certainly the main point, a harmonious family will bring a comfortable, safe, peaceful and peaceful atmosphere in contrast to a less harmonious family which often occurs in disputes, fights, differences of opinion, to acts of violence, this will have the potential to be bad for the psychology and development of children. In this case, a broken family can be seen from two aspects, namely: (1) the family is divided because the structure is not intact because one of the heads of the family has died or has been divorced; (2) the parents are not divorced but the family structure is no longer intact because the father or mother is often not at home, and does not pay attention to affectionate relationships anymore. The impact of these factors is that children who come from broken home families will be very vulnerable to committing deviant behavior at school with poor self-adjustment, such as lazy to study, aloof, aggressive, truant and likes to oppose teachers. The purpose of this study is to determine whether there is an influence from a broken home family on student deviant behavior at SMP Negeri 2 Plered. The research was conducted using a quantitative approach with the research method used, namely causal quantitative. The data collection technique was carried out by distributing questionnaires (questionnaires) to 32 students as a sample with a total of 28 questionnaires that had been tested for validity and reliability on variables (x) and (y). The research results show that: first, the level of broken home families is said to be quite high at a percentage of 73%. Second, the deviant behavior of students at SMP Negeri 2 Plered is quite high at a percentage of 72%. Third, that there is a negative and significant effect between the broken home family variable (x) on student deviant behavior (y) at SMP Negeri 2 Plered with a correlation value of -0.373 and the percentage of the relationship is 13.9% and 86.1% is influenced by the variable other.